Analysis of lexical acquisition in foreign languages through video games (2017)
Softwares as video games allow a virtual interaction with characters and environments which belong to the proper system, and these programs in turn need of an electronic device for its execution. Eguía argues (2012), video games promote a constructivist experience, which is defined as the foundation of an idea through students’ participation in didactical processes. Piaget Explains (1969) the process of knowledge is inherent in human reasoning, more specifically since childhood. The absorption of insight works from the first stages of children by means of experiences, which give them a meaning or a symbol to an action. For instance, take the hand of an adult express a way of conduction to the child. This philosophy of knowledge obtained by own experiences and discoveries is well-known as constructivism. Video games works as entertainment systems, but also could be a good instrument to develop different skills. As Sedeño interprets (2010), video games foment reflection and strategic thinking and these help to stimulate levels of mental agility.